Change of sea reclamation and the sea-use management policy system in China. (May 2020) - Li, Feixue; Ding, Dongdong; Chen, Zhenjie; Chen, Honghua; Shen, Ting; Wu, Qianlian; Zhang, Chenye
Abstract: Coastal reclamation has been regarded as an effective means to provide space for urban expansion and industrial development in China, given its low cost and flexible utilization. The Chinese government has issued a series of policies to boost or slow down reclamation to cope with varied conditions of domestic and international environments for China's economic development and marine environment problems. This paper aims to improve Chinese sea use management policy by analyzing reclamation area, the introduction of policies, and the impacts of these policies on reclamation from 2002 to 2018. First, statistical data and remote sensing data are used for analyzing the reclamation area and the construction area of the reclaimed land in the coastal areas of China. The results show that China reclaimed 2976.1 km 2 from the sea, of which 910.8 km 2 was constructed for urbanization and industrialization during 2002–2018. Whilst the statistical data from the Sea-Use Bulletin show that 1449.4 km 2 reclamation area was issued sea area user's right. The results indicate an increased trend of annual reclamation area from 2002 to 2015, a relatively stable annual construction area, and a declining construction ratio. Second, we connect the reclamation change and the change of the policy system following a review on the sea use management policy system. The analysis demonstrates that the stability and predictability of the policy system need improvement. Special efforts should be devoted to reinforcing law enforcement supervision and the concept of sustainable sea use should be advocated. Highlights: We analyze coastal reclamation area and the construction area of the reclaimed land in China from 2002 to 2018. The sea use management policy system in China has changed gradually from development-oriented to marine sustainability. China reclaimed 2976 km 2 from the sea and 910 km 2 was constructed for urbanization and industrialization from 2002 to 2018. Annual reclamation area showed an increased trend from 2012 to 2015 with a stable annual construction area from 2002 to 2018. The analysis of the reclamation change and the policy system shows the stability of the policy system needs improvement.